University Students Awareness of LMS and LCMS - Baharin, Ahmad Tajudin; Mat Yusof, Sharmila; Alaslam, Ahmad; Omar, Nazaruddin (Medwell Publishing, 2017)
Technology revolution has taken a great impact and profoundly influenced in higher education worldwide. Educational institutes positively invested to the internet and technology infrastructures as a tool to enhance teaching and learning program. Learning Management System (LMS) and Learning Content Management System (LCMS) are two types of educational tool used for learning purpose. Generally, LMS and LCMS have several similarities and benefits. Thus, this study aims to investigate the functions differences of LMS and LCMS. Furthermore, the study offers students awareness towards the usage of LCMS. The LMS and LCMS literature are reviewed to understand the functional criterions and benefits. Later, the both systems are compared. A total of 40 students from Universiti Utara Malaysia were identified to study the awareness of LCMS. The study reveals the students known the existence and the availabilities of LCMS to them.